2022
DOI: 10.1146/annurev-food-052720-010354
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenol–Polysaccharide Complex: Preparation, Characterization, and Potential Utilization in Food and Health

Abstract: Polysaccharides and polyphenols coexist in many plant-based food products. Polyphenol–polysaccharide interactions may affect the physicochemical, functional, and physiological properties, such as digestibility, bioavailability, and stability, of plant-based foods. In this review, the interactions (physically or covalently linked) between the selected polysaccharides and polyphenols are summarized. The preparation and structural characterization of the polyphenol–polysaccharide conjugates, their structural–inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(21 citation statements)
references
References 146 publications
0
17
0
Order By: Relevance
“…In addition, the interaction between polysaccharidepolyphenols in S.M. extract and starch could reduce the aggregation of starch (Guo et al, 2022). In the baking process, the high temperature made the starch molecules break and decreased the hardness of biscuits found that the hardness of biscuits decreased with the addition of four different oleogels; the effect of S.M.…”
Section: Texture Of Biscuitsmentioning
confidence: 99%
“…In addition, the interaction between polysaccharidepolyphenols in S.M. extract and starch could reduce the aggregation of starch (Guo et al, 2022). In the baking process, the high temperature made the starch molecules break and decreased the hardness of biscuits found that the hardness of biscuits decreased with the addition of four different oleogels; the effect of S.M.…”
Section: Texture Of Biscuitsmentioning
confidence: 99%
“…51 CPSs could interact with multiple polyphenols to modify several functions of polysaccharides. 52 Arabinoxylan (AX) and ferulic acid (FA) groups are often esterified with Arfa (arabinofuranosyl) residues. 53 It is reported that AX has the potential to prevent cancer, which may be related to FA.…”
Section: ■ Polysaccharides and Cancersmentioning
confidence: 99%
“…Cell wall polysaccharides (CPSs) are non-starch polysaccharides and important sources of dietary fiber . CPSs could interact with multiple polyphenols to modify several functions of polysaccharides . Arabinoxylan (AX) and ferulic acid (FA) groups are often esterified with Arfa (arabinofuranosyl) residues .…”
Section: Polysaccharides and Cancersmentioning
confidence: 99%
“…5 In this case, the smaller surface of nanoparticles (NPs) exposes the encapsulated polyphenols to a lower level of environmental stress. 4,6 The sustained release profile helps in maintaining stable blood concentrations and reducing toxic side effects, 7 thereby improving the oral bioavailability and enhancing therapeutic effects. Among all the reported delivery vehicles used for poorly soluble nutraceuticals/drugs, prolamins have attracted a certain degree of interest from the scientific community due to their biodegradability, biocompatibility, and renewability.…”
Section: Introductionmentioning
confidence: 99%